Jaringan Kerjasama Perpustakaan Lapangan - Yusniah Yusniah; Nurmala Lubis; Nurul Adilla; Imam Hardani Ritonga (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
According to UNESCO, one out of every 1000 Indonesians is interested in reading. This study shows that a lack of interest in reading can be an indication of a lack of awareness of Indonesian culture. According to the Central Bureau of Statistics, 4-5 hours a week is the same as the time for collecting and submitting collections of achievements for making collections of printed and recorded works in 2022 of 2,939,008 copies, which are in the National Library and libraries in the regions. It signifies that we will fulfill the demands of our desire to collect small reading books; You could say 1:90, or one book for every 90 people, right? This has contributed to the low literacy rate in Indonesia. Keywords Collaboration , Library , Field Network , Cooperation Network , Library Cooperation .